Comparacion de distintas leguminosas como cobertura en el cultivo de los citricos - Rodriguez, B.O.=700 1 Sosa, J.
(Es, En)
Ilus., 7 ref.
Keywords: CITRUS; LEGUMINOSAS; PLANTAS DE COBERTURA; CITRUS; CUBA